Implementation and Challenges of Online Learning in Early Childhood Education Post Covid-19 Pandemic - A. Nongko, Pahenra; Said, Hasmira; La Ndibo, Yaman; J. Deluma, Ridwan; Parida, Parida (Journal of Education Research, 2024)
This study highlights the importance of implementing an appropriate learning system to achieve learning objectives, especially in the context of early childhood education post-covid-19. This study aims to determine the implementation and challenges faced by teachers and parents in online learning post-covid-19. Using a descriptive qualitative research method, data collection was carried out through observation, interviews, and Google Forms, and analyzed using the triangulation method. The results showed various challenges such as limited facilities and infrastructure, lack of understanding of teachers and parents, and less than optimal collaboration. In addition, the condition of the child and the limitations of the media used are also obstacles. This study suggests that teachers need to facilitate internet networks and understand the characteristics of effective online learning. The main indicators of successful online learning for early childhood include the presentation of appropriate materials, the use of appropriate methods and media, and clear assessment strategies. This implementation is important to ensure that children still get an optimal learning experience even though it is done online.